MgF2 prism/rhodium/graphene: efficient refractive index sensing structure in optical domain. (27th February 2017) - Mishra, Akhilesh Kumar; Mishra, Satyendra Kumar
Abstract: A theoretical study of a noble surface plasmon resonance (SPR) based sensing probe has been carried out. The sensing probe consists of a magnesium fluoride (MgF2 ) prism with its base coated with rarely used noble metal rhodium (Rh) and a bio-compatible layer of graphene. The refractive indices (RIs) of the sensing medium vary from 1.33 to 1.36 refractive index unit (RIU). The thickness of Rh and the number of graphene layers have been optimized for maximum sensitivity in a constraint set by the detection accuracy (DA). For the operating wavelength of 632 nm, the optimized sensing probe Rh (12 nm)/graphene (single layer) demonstrates sensitivity of ~259 degree/RIU with corresponding DA of ~0.32 degree −1 while for 532 nm of excitation, the optimized sensing probe Rh (12 nm)/graphene (three layer) exhibits sensitivity of ~240 degree/RIU and DA of ~0.27 degree −1 .